Nanoparticles encapsulation - Ibrahim Ali , Noorbatcha (2015)
The small size along with the novel optical, electronic, and structural properties of nanoparticles that are not obtainable in discrete molecules or bulk solids, can be exploited to design customizable, targeted drug delivery systems capable of carrying different doses of drugs to the desired destination. Certain drugs can be carried as prodrugs or inactive drugs, which on reaching the target, can be converted to become active. Alternatively, the drugs in the nanoparticle form can be conjugated with the targeting moiety, leading to the accumulation of conjugated nanoparticles in the target site. As a result the concentration of the drug at the target can reach 10 to 100 times more than dosage obtained by the direct administration of the drug.